Ekuitas Layanan Rawat Inap Rumah Sakit di Indonesia - Ariani, Devi Senja; Pujiyanto, Pujiyanto (Jurnal Ekonomi Kesehatan Indonesia, 2019)
In order to encourage the achievement of UHC in Indonesia, the government organized National Health Insurance (JKN) program. One of the objectives of the JKN program is the improvement of access and equity utilization of health services. This study aims to analyze Equity of Inpatient Utilization in Health Service in second and third year of JKN program implementation in 2015 and 2016. This study uses secondary data of SUSENAS in 2015 and 2016 with analysis using concentration curve and concentration index. The results showed that the Utilization of inpatient services in hospitals in the JKN group of participants increased in 2015 to 2016. The richer population utilizes more Health Service than the poor, as evidenced by concentration curves below the diagonal line (equity line) and the value of the positive concentration index of 0.0336 in 2015 and 0.0382 in 2016. There was an increase in inequity utilization in inpatient services in 2015 to 2016 which was seen from the difference of concentration index value of 0.0045. Pro-rich inequity caused by inequalities in age, income, education, regional residence and JKN ownership. While sex and job variables reduce inequality in inpatient service utilization in hospital by 2015 and 2016.